Al- fatāwā at-tātārẖānīyah - Andarītī ad-Dihlawī al-Hindī, ʿĀlim Ibn-al-ʿAlāʾ al- - (Daʾiratuʾl-Maʿarifiʾl-Osmania (Osmania Oriental Publ. Bureau), Osmania Univ., 1984)
al-juzʼ 1. al-Muqaddimah. al-Ṭahārah. al-Ṣalāh -- al-juzʼ 2. al-Ṣalāh. al-Zakāt. al-Ṣawm. al-Ḥajj. al-Nikāḥ -- al-juzʼ 3. al-Nikāḥ. al-Riḍāʻ. al-Ṭalāq -- al-juzʼ 4. al-Ṭalāq. al-ʻItāq. al-Īmān -- al-juzʼ 5. al-Īmān. al-Ḥudūd. al-Sariqah. al-Sayr. al-Kharāj. al-Laqīṭ. al-Shirkah. al-Waqf